Water quality. Biological methods. Determination of the acute lethal toxicity of substances to a freshwater fish [Brachydanio rerio Hamilton-Buchanan (Teleostei, Cyprinidae)]: static method Part 5-5.2, (31st December 1985) - British Standards Institution,
No abstract available